Effect of gender, leg dominancy and body mass index on Y-balance performance among young healthy adults - Ewais, Najlaa Fathi; Abdel-Aziem, Amr Almaz; Hassan, Sahar Mahmoud (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study investigated the influence of the sex, dominant leg and BMI on dynamic balance control of young adults (mean age; 20 ± 1.56) using the Y-balance test-lower quarter (YBT-LQ). This cross-sectional study included 218 participants (105 men and 103 women) who were recruited as a convenient sample of young, normal adults. The examination was implemented in one session, with three trials in each direction on each leg. The maximum reach distance of the three trials in each direction was used for statistical analysis. The reported reach distances were also normalized for each participant’s leg length. Males’ right leg values in the posteromedial (PM), posterolateral (PL), and composite directions were substantially longer than females’ (p<0.05), and no significant difference between both sexes in anterior (AT) direction (p>0.05). In all directions, there were no significant differences between both sexes for the left leg (p>0.05), and no significant differences between the right values of the dominant and non-dominant legs (p>0.05). However, the left values of the non-dominant legs were longer than the dominant leg in directions (p<0.05). The right leg values of the AT, PM, and composite values of the average BMI subjects was greater than the over-weight and obese subjects (p<0.05), and the left leg values of the AT and composite values of the average BMI subjects was greater than over-weight and obese subjects (p<0.05). Males have a longer right leg reach distance in the PM, PL directions, and composite value compared to females. The right leg dominant participants have longer reach distance of the left leg in all directions. When compared to over-weight and obese participants, average body weight subjects have bilaterally larger reach distance in the AT and composite directions.